Effect of Al Speciation on the Structure of High‐Al Steels Mold Fluxes Containing Fluoride. Issue 12 (24th August 2016) - Gao, Jinxing; Wen, Guanghua; Huang, Ting; Bai, Binwen; Tang, Ping; Liu, Qiang
Abstract : To design suitable mold fluxes for the casting of high‐Al steels, the structure of mold fluxes based on CaO–SiO2, CaO–SiO2 –Al2 O3, and CaO–Al2 O3 was examined by Raman spectroscopy and magic‐angle spinning nuclear magnetic resonance. The results showed that Si atoms are replaced by Al atoms as the network formers with the increase in Al2 O3 in the mold fluxes. This converts the silicate slags (CaO–SiO2 mold fluxes) into aluminosilicates slags (CaO–SiO2 –Al2 O3 or CaO–Al2 O3 mold fluxes). The F − ions in the mold flux containing Al2 O3 are classified into three categories, according to function: Bridging F's, Nonbridging F's, and Free‐F's. The Al 3+ ion holds three distinct coordination environments: IV Al, V Al, and VI Al. The addition of F affects the coordination environment of Al 3+ to form AlO3 F and AlO2 F2 that accommodate the network structure of slags. The network structure in the CaO–SiO2 mold fluxes is mainly connected through Si–O–Si linkage. However, the network structure of the mold fluxes containing elevated content of Al2 O3 is mainly connected through Si–O–Si, Al–O–Al, Al–O–Si, and Al–F–Al linkages. Hence, the structural characteristics of high‐Al steels mold fluxes must be considered during the designing step of the mold fluxes.